2014
DOI: 10.1097/der.0000000000000025
|View full text |Cite
|
Sign up to set email alerts
|

Benzophenones

Abstract: Benzophenones are ultraviolet light filters that have been documented to cause a myriad of adverse cutaneous reactions, including contact and photocontact dermatitis, contact and photocontact urticaria, and anaphylaxis. In recent years, they have become particularly well known for their ability to induce allergy and photoallergy. Topical sunscreens and other cosmetics are the sources of these allergens in most patients, but reports of reactions secondary to use of industrial products also exist. Benzophenones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 43 publications
0
47
0
Order By: Relevance
“…Cross‐reactions within the benzophenone family have not been proven; however, they are feasible, given the similar chemical structures . All of the three previously reported cases of benzophenone‐3 anaphylactic reactions included only one benzophenone, whereas our patient had reactions to three benzophenones .…”
Section: Discussionmentioning
confidence: 71%
“…Cross‐reactions within the benzophenone family have not been proven; however, they are feasible, given the similar chemical structures . All of the three previously reported cases of benzophenone‐3 anaphylactic reactions included only one benzophenone, whereas our patient had reactions to three benzophenones .…”
Section: Discussionmentioning
confidence: 71%
“…Benzophenones are chemical UV light absorbers used in sunscreens and cosmetic and industrial products to reduce photodegradation. Benzophenones were named Contact Allergen of the Year by the American Contact Dermatitis Society in 2014 to raise awareness of allergic contact dermatitis (ACD) and PACD caused by these ubiquitous aromatic ketones . Benzophenone identified in our patient's goggles has recently been recognized as the culprit allergen in plastic amusement park wristbands 3 and is the simplest and non‐derivatized member of the benzophenone‐type UV‐absorbers.…”
Section: Discussionmentioning
confidence: 98%
“…Sensitivity to benzophenone-2 and benzophenone-8 is exceedingly rare 1 with only 1 other reported case to benzophenone-2 4 and 2 cases to benzophenone-8. 1 Cross-reactivity between benzophenones is conceivable given their shared chemical structure (Fig. 3) but has not been well documented in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…1 This group of chemicals is found not only in sunscreen products but is widely used in both cosmetics (eg, shampoos, moisturizers) and industrial products (eg, paints, varnishes) to prevent photodegradation. In our clinic, we have found that approximately a third of lip ACD in our patients is due to sunscreen agents (much higher than 5%Y7.4% in published studies 2 ) and we now routinely test the sunscreen series in all of our patients with lip dermatitis.…”
Section: Discussionmentioning
confidence: 99%